2023
DOI: 10.1055/a-2127-0690
|View full text |Cite
|
Sign up to set email alerts
|

The Report of Community-Based and Government-Endorsed Screening Program of Atrial Fibrillation in Taiwan

Tze-Fan Chao,
Yung-Hsin Yeh,
Yi-Hsin Chan
et al.

Abstract: Background: The community-based AF screening program incorporated into the government-endorsed health care system is rarely reported in Asian countries. Objectives: We aimed to test the feasibility of adding AF screening into the preexistent adult health check program, report the AF detection rate and percentages of OAC prescriptions before and after AF screening with the involvement of public health care system. Methods: We performed this program in 3 counties in Taiwan which have their own official preexis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Considering all the above AF related complications, efforts have been made to reduce the healthcare burden by use of screening focused on high risk populations, 33 or targeted at community based screening programmes. 34 Importantly, while early AF diagnosis is intended to detect AF among individuals with AF-related symptoms, screening invites individuals without AF-related symptoms to undergo testing. 35 A recent meta-analysis of 4 RCTs (REHEARSE-AF, SCREEN-AF, LOOP and STROKESTOP) with a total of 35,836 participants indicated that AF screening was associated with a reduction in stroke as compared with no screening, (RR 0.91, 95% CI 0.84–0.99).…”
Section: Atrial Fibrillation Screeningmentioning
confidence: 99%
“…Considering all the above AF related complications, efforts have been made to reduce the healthcare burden by use of screening focused on high risk populations, 33 or targeted at community based screening programmes. 34 Importantly, while early AF diagnosis is intended to detect AF among individuals with AF-related symptoms, screening invites individuals without AF-related symptoms to undergo testing. 35 A recent meta-analysis of 4 RCTs (REHEARSE-AF, SCREEN-AF, LOOP and STROKESTOP) with a total of 35,836 participants indicated that AF screening was associated with a reduction in stroke as compared with no screening, (RR 0.91, 95% CI 0.84–0.99).…”
Section: Atrial Fibrillation Screeningmentioning
confidence: 99%